Brain basis of childhood speech and language disorders: are we closer to clinically meaningful MRI markers?. Issue 6 (December 2016) - Morgan, Angela; Bonthrone, Alexandra; Liégeois, Frédérique J.
Abstract : Purpose of review: Developmental speech and language disorders are common, seen in one in 20 preschool children, in the absence of frank neurological deficits or intellectual impairment. They are a key reason parents seek help from paediatricians. Complex neurogenetic and environmental contributions underpin the disorders, yet few specific causes are known. With the advent of quantitative brain imaging, a growing number of studies have investigated neural contributions. Here, we discuss current MRI approaches and recent findings (January 2014–June 2016) in the field. Recent findings: Five relevant studies were identified ( n = 3 – speech disorder and n = 2 – language disorder). Significant variability in MRI approaches and heterogeneity of participant phenotypes was seen. Children with speech disorder had structural and functional anomalies in the left supramarginal gyrus and functional anomalies in the posterior cerebellum bilaterally – regions critical for sensory–motor integration or feedback. Children with language disorder showed increased mean and radial diffusivity of the left arcuate fasciculus, although a widespread cortical and subcortical network of regions was implicated. Summary: Limited evidence exists for specific regional brain anomalies in this population. MRI prognostic markers of speech and language ability are not currently available at an individual level. Further work is required to disentangle neurobiological contributions to speech and language disorders for affected children. Abstract : Supplemental Digital Content is available in the text